Health effects of psychological interventions for worry and rumination: A meta-analysis - McCarrick, Dane; Prestwich, Andrew; Prudenzi, Arianna; O'Connor, Daryl B (Health psychology, 2021)
Evidence suggests that perseverative cognition (PC), the cognitive representation of past stressful events (rumination) or feared future events (worry), mediates the relationship between stress and physical disease. However, the experimental evidence testing methods to influence PC and the subsequent relationship with health outcomes has not been synthesized. Therefore, the current review addressed these gaps. Studies randomly assigning participants to treatment and control groups, measuring PC and a physical and/or behavioral health outcome after exposure to a nonpharmacological intervention, were included in a systematic review. Key terms were searched in Medline, PsycINFO and CINAHL databases. Of the screened studies ( = 10,703), 36 met the eligibility criteria. Random-effects meta-analyses revealed the interventions, relative to comparison groups, on average produced medium-sized effects on rumination ( = -.58), small-to-medium sized effects on worry ( = -.41) and health behaviors ( = .31), and small-sized effects on physical health outcomes ( = .23). Effect sizes for PC were negatively associated with effect sizes for health behaviors. (following outlier removal). Effect sizes for PC were significantly larger when interventions were delivered by health care professionals than when delivered via all other methods. No specific intervention type (when directly compared against other types) was associated with larger effect sizes for PC. Psychological interventions can influence PC. Medium-sized (negative) effect sizes for PC correspond with small (but positive) health behavior effect sizes. (PsycInfo Database Record (c) 2021 APA, all rights reserved).